Determinant Of Rating Corporation Sukuk In Emerging Market - Alghifari, Huzeini; Falikhatun, Falikhatun (ITB AAS INDONESIA Surakarta, 2024)
The aim of this study is to investigate the impact of profitability, board size, and institutional ownership on corporate sukuk ratings. The data analysed in this research is secondary. Companies listed on the Indonesia Stock Exchange and Bursa Malaysia, which issue sukuk and are rated by PT PEFINDO and MARC Berhad between 2015 and 2021 constitute the population. The sampling method employed is purposive. The panel data regression technique is the analytical method utilised in this study, with Eviews 10 software as the tool. The outcome of the analysis show that corporate sukuk ratings are significantly affected by board size and institutional ownership, while profitability has no effect on them.